2015
DOI: 10.1371/journal.pone.0126985
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Computed Tomography for Chronic Thromboembolic Pulmonary Hypertension: A Systematic Review and Meta-Analysis

Abstract: This study aimed to determine the diagnostic accuracy of computed tomography imaging for the diagnosis of chronic thromboembolic pulmonary hypertension (CTEPH). Additionally, the effect of test and study characteristics was explored. Studies published between 1990 and 2015 identified by PubMed, OVID search and citation tracking were examined. Of the 613 citations, 11 articles (n=712) met the inclusion criteria. The patient-based analysis demonstrated a pooled sensitivity of 76% (95% confidence interval [CI]: 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 35 publications
1
39
2
7
Order By: Relevance
“…This technique requires high levels of expertise and is used mostly in experienced centres [15]. Recent studies have suggested that CT and magnetic resonance pulmonary angiography are superior to traditional pulmonary angiography methods in mapping lesions in proximal and segmental vessels [15,24,25].…”
Section: Imaging Of the Pulmonary Vasculaturementioning
confidence: 99%
“…This technique requires high levels of expertise and is used mostly in experienced centres [15]. Recent studies have suggested that CT and magnetic resonance pulmonary angiography are superior to traditional pulmonary angiography methods in mapping lesions in proximal and segmental vessels [15,24,25].…”
Section: Imaging Of the Pulmonary Vasculaturementioning
confidence: 99%
“…After installation of dual-energy CT in routine clinical practice, clinicians have been able to effectively identify this perfusion abnormality on iodine maps derived from dual-energy CT data. Furthermore, a meta-analysis reported on the capability of contrast-enhanced CTA with and without dual-energy CT or electrocardiogram-gated ADCT information for CTEPH patients (103). In this study, the patient-based analysis demonstrated a pooled sensitivity of 76%, a pooled specificity of 96%, and a pooled diagnostic odds ratio of 191.…”
Section: Dual-energy Ctmentioning
confidence: 64%
“…Since MDCT can examine segmental and subsegmental arterial branches, it also guides the treatment process. In addition, it provides assistance concerning pulmonary angioplasty in the presence of chronic thromboembolism in subsegmental arterial branches …”
Section: Discussionmentioning
confidence: 99%
“…In addition, it provides assistance concerning pulmonary angioplasty in the presence of chronic thromboembolism in subsegmental arterial branches. 11 The pulmonary vascular CT signs for CTEPH include >29 mm diameter of the main pulmonary artery, circumferential thrombus (wide angle) along with the vessel wall, calcification of thrombus, membranes and septa within the branches of the pulmonary arteries, narrowing and thinning of the distal pulmonary arterial branches and total occlusion. The cardiac signs of CTEPH revealed by CT are increased right ventricular diameter, bowing of the septum and right atrium enlargement.…”
Section: Discussionmentioning
confidence: 99%